Idiopathic delayed-onset edema surrounding deep brain stimulation leads: Insights from a case series and systematic literature review. (November 2016) - de Cuba, Catherine M.K.E.; Albanese, Alberto; Antonini, Angelo; Cossu, Giovanni; Deuschl, Günther; Eleopra, Roberto; Galati, Alejandro; Hoffmann, Carel F.E.; Knudsen, Karina; Landi, Andrea; Lanotte, Michele Maria R.; Marcante, Andrea; et al.
Abstract: Introduction: Deep brain stimulation (DBS) is effective for some neurological and psychiatric conditions. Idiopathic delayed-onset edema (IDE) surrounding the leads has been anecdotally reported. The etiology, predisposing factors and prognosis of this complication are unknown. We present a multicenter case series of patients with IDE, and a systematic literature review, aimed at defining the pathophysiology and identifying appropriate treatment strategies. Methods: IDE was defined as edema along the DBS lead, occurring ≥72 h postoperatively, in absence of trauma, vascular events or infection. Information on patients with IDE was collected in a standardized way. A systematic search was performed in Pubmed. Results: Twelve new patients presenting with 14 episodes of IDE are described. From the literature, 38 patients were identified. No common surgical aspects or patient-related factors were identified as risk predictors for the onset of IDE. Symptoms included deterioration of the stimulation effect, seizures and focal neurological signs. Although the condition is self-limiting, with symptoms resolution in 28.5 days on average, three patients underwent surgical revision and seven received antibiotics. Conclusions: IDE is a rare complication of DBS procedures, presenting from few days to months after surgery. Symptoms can be mild and not-specific, and the condition is self-limiting. The diagnosis of IDE is made after exclusion of vascular events or infections. The pathophysiology is still unexplained. The recognition of this complication can help avoiding unnecessary surgical procedures (system explantation) and antibiotic treatment. Highlights: Idiopathic delayed-onset edema (IDE) is a rare complication of deep brain stimulation (DBS). IDE develops along the DBS lead ≥72 h postoperatively, in absence of trauma, vascular events or infection. The pathophysiology is still unexplained. IDE is self-limiting; steroids might shorten recovery time. Switching off stimulation or constant-current stimulation should be considered.